Los juegos predeportivos como medio para la promoción y masificación del mini voleibol de la escuela Benigno Bayancela de la ciudad de Loja periodo 2016-2017 - Cholango Morocho, José Luis (2018)
The present investigation titled THE PREDEPORTIVE GAMES AS MEANS FOR THE PROMOTION AND MASIFICATION OF THE MINI VOLLEYBALL OF THE SCHOOL BENIGNO BAYANCELA OF THE CITY OF LOJA PERIOD 2016-2017. The central problem to investigate is how does the predeportive games affect the promotion and massification of the mini volleyball in the school Benigno Bayancela of the city of Loja period 2016-2017 ?, its objective is framed in elaborating a proposal of a program of predeportive games for the promotion and massification of the mini volleyball in the students of the school Benigno Bayancela of the city of Loja period 2016-2017., It focuses scientifically on two variables, in the promotion and massification of mini volleyball. During this process the Scientific, deductive, synthetic, hypothetical and descriptive method, techniques and instruments such as the interview and the initial and final observation were applied, with all the information arsenal of the application of the instruments, the following conclusion could be reached: Lack of knowledge of mini volleyball and its importance that recreational physical activities to improve the quality of life, in addition to the shortage of trained professionals in physical culture if it influences the practice of mini volleyball since firstly it is not disclosed in the way indicated to be able to practice it and thus improve their quality of life. The results were that 100% of the children of the school Benign Bayancela improved each of the technical foundations of the mini volleyball, which would like to continue participating in the program of predeportive games to promote and massify the mini volleyball, thus making better use of their free time and improve their quality of life.